2010
DOI: 10.3109/03014460903563442
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual characteristics: A study of the adolescents of rural and urban West Bengal, India

Abstract: Menstrual characteristics differ significantly between rural and urban adolescents. Moreover, various socio-economic variables pertaining to place of residence significantly affect the menstrual characteristics among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
4
16
1
Order By: Relevance
“…However, internet was the main sources of knowledge (81.2%) among urban adolescents, whereas among rural adolescents girl's mother was the main sources of knowledge regarding menstruation. A study done by Sadiq 13,20,26,[28][29][30] The important finding reported in this study is that teachers were not considered neither as a good source of information nor were they preferred to provide education regarding these matters. Most common problem was abdominal pain, followed by pain in leg, headache/Irritation, and Loss of Appetite.…”
Section: Discussionmentioning
confidence: 88%
“…However, internet was the main sources of knowledge (81.2%) among urban adolescents, whereas among rural adolescents girl's mother was the main sources of knowledge regarding menstruation. A study done by Sadiq 13,20,26,[28][29][30] The important finding reported in this study is that teachers were not considered neither as a good source of information nor were they preferred to provide education regarding these matters. Most common problem was abdominal pain, followed by pain in leg, headache/Irritation, and Loss of Appetite.…”
Section: Discussionmentioning
confidence: 88%
“…Additional evidence for earlier age at menarche in urban girls (at 12.0, 12.6, and 13.6 years) and at later ages among rural samples (14.1, 13.5, and 12.8 years) is cited by Deo and Gattarji (2004). In West Bengal, urban girls experience menarche earlier (mean 5 11.4, SD 1.03 years) than those living in rural settings (mean 5 12.1, SD 1.15 years, P < 0.001) (Ray et al, 2010). A study of age at menarche in New Delhi among an endogamous group known as Aroras from Punjab State, found evidence of a secular trend in menarche (Khanna and Kapoor, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Extensive data on age at menarche is available for South Asian populations and reveals a pattern that is consistent with the US data, yet exhibits a wide range of variation. A representative selection of studies on age at menarche in South Asia document a range in mean age between 11.8 years in urban West Bengal (Ray et al, 2010) to 14.4 years in rural Perideniya, Sri Lanka (World Health Organization, 1986. The median age at menarche in a sample of 96 girls from Dharan, southeastern Nepal, is 12 years (Sharma and Gupta, 2003), while the mean age in a periurban sample of 260 girls from 60 km north of Kolkata is 12.8 years (SD 1.12) (Sanyal and Ray, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…According to the Iranian Statistical Center, there are more than 4,000 children in boarding centers in Tehran, the capital city of Iran (8). A comparison between girls living in welfare boarding centers and those who stayed with their families showed statistically significant difference in health behavior regarding hygienic practices during menstruation; lower scores were obtained among girls living in welfare boarding centers (9).…”
Section: Introductionmentioning
confidence: 88%